PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA - Maritua Simatupang (JURNAL GLOBAL EDUKASI, 2019)
Abstract: The purpose of this study was to determine the application of the Problem Solving learning model to improve student learning outcomes in learning Physics of Global Warming Symptoms in class XI of SMA Negeri 1 Pahae Julu in the academic year 2018/2019. This research is a classroom action research, with research subjects of class XI students of SMA Negeri 1 Pahae Julu, totaling 30 people. The object of this research is student learning outcomes through the application of the Problem Solving Method Approach. The instrument used was a multiple choice test consisting of 10 items. The results showed that in the first cycle there were 22 students who completed or 73.33% of the 30 students who took the test. The mastery level of students in the first cycle of 73.67% is in the category of "moderate" and the percentage of student activity of 70% is in the sufficient category. In cycle II there were 27 students who completed or 90.00% of the 30 students who took the test. The level of mastery of students in the second cycle of 80.67% was in the "high" category and the percentage of student activities of 84% was in the good category. It can be concluded that the application of the Problem Solving learning model can improve student learning outcomes in learning Physics of Global Warming Symptoms in class XI of SMA Negeri 1 Pahae Julu academic year 2018/2019.Â Keywords: problem solving, global warmingÂ Â Abstrak: Tujuan penelitian ini adalah untuk mengetahui penerapan model pembelajaranÂ  Problem Solving dapat meningkatkan hasil belajar siswa pada pembelajaran Fisika materi Gejala Pemanasan Global di kelas XI SMA Negeri 1 Pahae Julu tahun pelajaran 2018/2019. Penelitian ini merupakan penelitian tindakan kelas, dengan subjek penelitianÂ  siswa kelas XI SMA Negeri 1 Pahae Julu yang berjumlah 30 orang. Objek dalam penelitian ini Â adalah hasil belajar siswa melalui PenerapanÂ  Pendekatan MetodeÂ  Problem Solving. Instrumen yang digunakan adalah tes berbentuk pilihan ganda yang terdiri dari 10 butir soal. Hasil penelitian menunjukkan bawah pada siklus I terdapat 22 orang siswa tuntas atau 73,33% dari 30 siswa yang mengikuti tes.Â  Tingkat penguasaan siswa pada siklus I sebesar 73,67% berada pada kategori â€œsedangâ€ danÂ  persentaseÂ  aktivitas siswa sebesar 70% berada pada kategori cukup.Â  Pada siklus II terdapat 27 orang siswa tuntasÂ  atau 90,00% dari 30 siswa yang mengikuti tes. Tingkat penguasaan siswa pada siklus II sebesar 80,67% berada pada kategori â€œtinggiâ€ danÂ  persentase aktivitas siswa sebesar 84% berada pada kategori baik. Dapat disimpulkanÂ  penerapan model pembelajaranÂ  Problem Solving dapat meningkatkan hasil belajar siswa pada pembelajaran Fisika materi Gejala Pemanasan Global di kelas XI SMA Negeri 1 Pahae Julu tahun pelajaran 2018/2019.Â Kata kunci: problem solving, pemanasan globalÂ